The Contribution of Mangrove Forest to Coastal Household Income in East Lombok, Indonesia - Muhamad Bai'ul Hak; Rusmin Nuryadin; Muhammad Dzul Fadlli; Al Furkan; Pahrudin Pahrudin; Dedi Kurniawan (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2026)
This study examines the contribution of mangrove ecosystems to coastal household income in Jerowaru Village, East Lombok, Indonesia, and evaluates how direct economic benefits shape community incentives for mangrove conservation. Positioned within the governance and development agenda, the study addresses the role of natural capital in supporting coastal welfare and nature-based development in an emerging economy context. A mixed-method design was employed using household questionnaires, direct interviews, and focus group discussions involving 115 respondents living near the mangrove area. The study applied a direct use-value and market-price approach to estimate household income from mangrove-related activities, including ecotourism, fish harvesting, crab and prawn collection, and firewood use. Willingness to pay was also assessed to capture community-level conservation incentives. The findings show that 87.8% of respondents receive direct economic benefits from mangrove resources, while 12.2% report no direct income contribution. Most households gain only IDR 100,000–250,000 per month, indicating that mangroves function mainly as a supplementary livelihood source. Despite high conservation awareness, willingness to pay remains limited, revealing a gap between ecological concern and economic incentives. This study contributes household-level evidence on mangrove ecosystem valuation in a small-island Indonesian setting. By linking direct-use valuation, livelihood dependence, and conservation incentives, it offers policy-relevant insights for community-based mangrove governance, coastal development, and nature-based strategies in Indonesia and comparable developing economies.